2018
DOI: 10.1126/scisignal.aao1815
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synapses without synaptic vesicles: Purinergic neurotransmission through a CALHM1 channel-mitochondrial signaling complex

Abstract: Conventional chemical synapses in the nervous system involve a presynaptic accumulation of neurotransmitter-containing vesicles, which fuse with the plasma membrane to release neurotransmitters that activate postsynaptic receptors. In taste buds, type II receptor cells do not have conventional synaptic features but nonetheless show regulated release of their afferent neurotransmitter, ATP, through a large-pore, voltage-gated channel, CALHM1. Immunohistochemistry revealed that CALHM1 was localized to points of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 52 publications
3
85
0
Order By: Relevance
“…Biocytin uptake and Cs + ‐insensitive currents were inhibited by the relatively nonselective CALHM1 blockers Gd 3+ and Zn 2+ but were not affected by another nonselective CALHM1 blocker, ruthenium red, or by pannexin 1 and Cx43 blockers. Biocytin uptake was observed after soaking the basolateral membranes of the TBCs, which is consistent with previous studies on CALHM1 channel expression (Kashio et al, ; Romanov et al, ). We confirmed the expression of CALHM1 and CALHM3 channel genes in fungiform taste buds using RT‐PCR.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Biocytin uptake and Cs + ‐insensitive currents were inhibited by the relatively nonselective CALHM1 blockers Gd 3+ and Zn 2+ but were not affected by another nonselective CALHM1 blocker, ruthenium red, or by pannexin 1 and Cx43 blockers. Biocytin uptake was observed after soaking the basolateral membranes of the TBCs, which is consistent with previous studies on CALHM1 channel expression (Kashio et al, ; Romanov et al, ). We confirmed the expression of CALHM1 and CALHM3 channel genes in fungiform taste buds using RT‐PCR.…”
Section: Discussionsupporting
confidence: 91%
“…CALHM channels and several types of Cx hemichannels are activated by the reduction of [Ca 2+ ] out and membrane depolarization. Recent studies have indicated that CALHM1 and CALHM1/3 complex channels are localized on the basolateral membrane in TBCs (Kashio et al, ; Romanov et al, ). In TBCs that express [Ca 2+ ] out ‐dependent channels on the basolateral membrane, extracellular biocytin is moved into the cells via the channels activated by reducing [Ca 2+ ] out .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations